2019
DOI: 10.1186/s12957-019-1617-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum zinc levels and lung cancer: a meta-analysis of observational studies

Abstract: Background Inconsistent results according to numerous studies that had investigated the association between serum zinc levels and lung cancer risk were reported. The aim of this study was to explore whether serum zinc levels were lower in lung cancer patients than that in controls. Methods We systematically retrieved the databases of PubMed, Wanfang, Cochrane, ScienceDirect website, CNKI, and SinoMed databases for comprehensive relevant studies published before December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 26 publications
4
24
0
1
Order By: Relevance
“…The results derived from this study are promising in terms of deepening of our knowledge of oncogenesis and providing assistance in the future treatment of colon cancer. Several studies have identified that low levels of serum Zn are a risk factor for many kinds of cancer (11,(13)(14)(15)20), including colon cancer (16). Our study further identified that the low level of serum Zn is risk factor of the prognosis of colon cancer.…”
Section: Discussionsupporting
confidence: 75%
“…The results derived from this study are promising in terms of deepening of our knowledge of oncogenesis and providing assistance in the future treatment of colon cancer. Several studies have identified that low levels of serum Zn are a risk factor for many kinds of cancer (11,(13)(14)(15)20), including colon cancer (16). Our study further identified that the low level of serum Zn is risk factor of the prognosis of colon cancer.…”
Section: Discussionsupporting
confidence: 75%
“…Comparable trends were reported in a current meta-analysis with respect to LC [ 73 ]. Here, 27 from 32 studies (including 2,894 cases and 9,419 controls), mostly from Asia (including three European studies), indicated lower serum Zn levels in LC patients than in controls (SMD = −0.88, p < 0.001), while in four and two studies no significant and a positive association, respectively, were recognized.…”
Section: Zincsupporting
confidence: 75%
“…Changes in blood zinc has been found in lymphoproliferative disorders as well as in breast, lung and gastrointestinal tumors [29]. Research indicates that the concentrations of zinc in the serum or plasma are low in people with cancer [30], which is consistent with severals study, which confirms that there is a strong relationship between low levels of zinc and cancer [31][32].…”
Section: Zinc In Cancer Diseasesupporting
confidence: 70%